Attitude and family support to family members who are having mental disorders at Community Health Center, Central Java, Indonesia - Tri Sumarsih; Irfanuddin Wakhid; Arnika Dwi Asti (International Journal of Health Science and Technology, 2019)
The phenomenon of mental disorders is currently experiencing a significant increase and always increase every year in various parts of the world. Family support is a form of providing support to other family members who experienced problems. The family influences the client's values, beliefs, attitudes and behavior. Based on data at Kutowinangun Health Center related to mental disorder patient visited in 2016 totaling 330 patients, the average number of monthly visit was around 11% or 28 patients. To find out family attitudes and support for family members who experienced mental disorders in Kutowinangun Health Center. This research is a descriptive study with a survey approach. The method of taking respondents in this study uses purposive sampling from the results of sample calculations obtained 75 respondents. Based on the research conducted, it was found that family attitudes toward family members who experience mental disorders in Kutowinangun Primary Health Center, the majority of the category is very good as many as 54 respondents (72,0%) and family support in the majority of good categories as many as 46 respondents (61,3% ). Nurses motivate families to invite family members with mental disorders to exercise control at the Kutowinangun Health Center and families to monitor medication regularly.